Combined Legendre Spectral-Finite Element Method for the Two-Dimensional Unsteady Navier-Stokes Equation (Journal of Computational Mathematics, 1999)
A combined Legenedre spectral-finite element approximation is proposed for solving two-dimensional unsteady Navier-Stokes equation. The artificial compressibility is used. The generalized stability and convergence are proved strictly. Some numerical results show the advantages of this method.
Keywords: Navier-Stokes equation; Combined Legendre spectral-finite element approximation.